Combining Readiness and Success Constructs for Exploring the Information System Implementation Performance: A Model Development - Cecep Nurul, Alam; Putra, S.J; Subaeki, B; Aedah, Abd Rahman; T.K.A, Rahman; Y, Suryana (2019)
This study explained how to combine the technology readiness and success model of information systems (IS) in the context of exploring the factors that influence the readiness and success of IS implementation performance. As explained by many studies of IS, that most IS research models are developed by adopting, combining, and adapting previous studies. The researchers developed this model based on the input-process-output logic and professional and causal models of the IS success model. The developed model was structured in twelve variables and 42 indicators. The path influences between variables were presented by 28 links. Researchers broke down the model to the level of the assessment instrument in relation to the implementation of the research. However, the model development study may have limited in the used assumptions and understanding of the researchers, the study may contribute theoretically in terms of new model propositions. In addition, the development of the proposed model and the instrument for data collection may be a practical consideration point for further study.